IMPROVEMENT AND STORAGE OF CONVENTIONAL MAMMOGRAPHY IMAGES USING TECHNIQUES OF DIGITAL IMAGE PROCESSING (Brazilian Journal of Radiation Sciences, 2015)
The aim of this work is to show that a computer program, called digital image processing (DIP), can be used as an alternative method for breast diagnosis in hospitals and clinics that have not yet computerized mammography service. The image of mammogram obtained in reference is used to demonstrate the usefulness of some techniques of the DIP computer program involving contrast enhancement, smoothing of noise and segmentation. These techniques were used to calculate the area of soft tissue that is being occupied by certain tumor. To implement the DIP techniques the mammography department needs to have a high-resolution scanner, a computer and the DIP software, which is an application, developed by the Grupo de Dosimetria Numérica (GDN). The images can be organized and stored into stacks of images in the standard format for 3D image on DIP and then processed to obtain an improvement. In this work, we used the nonlinear median filter to remove noise or artifacts of the original image. Linear functions have also been used to improve contrast and sharpest of the image. Using segmentation and logical operations the area where the tumor is located in the image will be treated and correspond to the shades of gray. Then, the pixels are computed aiming to calculate the percentage of soft tissue that is occupied by the tumor.
Keywords: Digital imaging processing; mammography; segmentation